Diagnosis and Management of Secondary HLH/MAS Following HSCT and CAR-T Cell Therapy in Adults; A Review of the Literature and a Survey of Practice Within EBMT Centres on Behalf of the Autoimmune Diseases Working Party (ADWP) and Transplant Complications Working Party (TCWP) - Sandler, Robert David; Tattersall, Rachel Scarlett; Schoemans, Helene; Greco, Raffaella; Badoglio, Manuela; Labopin, Myriam; Alexander, Tobias; Kirgizov, Kirill; Rovira, Montserrat; Saif, Muhammad; Saccardi, Riccardo; Delgado, Julio; et al. (Frontiers in Immunology, 2020)
Introduction Secondary haemophagocytic lymphohistiocytosis (sHLH) or Macrophage Activation Syndrome (MAS) is a life-threatening hyperinflammatory syndrome that can occur in patients with severe infections, malignancy or autoimmune diseases. It is also a rare complication of haematopoetic stem cell transplantation (HSCT), with a high mortality. It may be associated with graft versus host disease in the allogeneic HSCT setting. It is also reported following CAR-T cell therapy, but differentiation from cytokine release syndrome (CRS) is challenging. Here we summarise the literature and present results of a survey of current awareness and practice in EBMT-affiliated centres of sHLH/MAS following HSCT and CAR-T cell therapy. Methods An online questionnaire was sent to the principal investigators of all EBMT member transplant centres treating adult patients (18 years and over) inviting them to provide information regarding: number of cases of sHLH/MAS seen in their centre over 3 years (2016-2018 inclusive); screening strategies and use of existing diagnostic/classification criteria and treatment protocols. Results 114/472 centres from 24 different countries responded (24%). We report estimated rates of sHLH/MAS of 1.09% (95% CI=0.89-1.30) following allogeneic HSCT, 0.15% (95% CI=0.09-5.89) following autologous HSCT and 3.48% (95% CI=0.95-6.01) following CAR-T cell therapy. A majority of centres (70%) did not use a standard screening protocol. Serum ferritin was the most commonly used screening marker at 78% of centres, followed by soluble IL-2 receptor (24%), triglycerides (15%) and fibrinogen (11%). There was significant variation in definition of “clinically significant” serum ferritin levels ranging from 500 to 10,000 μg/mL. The most commonly used criteria to support diagnosis were HLH-2004 (43%) and the H score (15%). Eighty percent of responders reported using no standard management protocol, but reported using combinations of corticosteroids, chemotherapeutic agents, cytokine blockade and monoclonal antibodies. Conclusions There is a remarkable lack of consistency between EBMT centres in the approach to screening, diagnosis and management. Further research in this field is needed to raise awareness of and inform harmonised, evidence-based approaches to the recognition and treatment of sHLH/MAS following HSCT/CAR-T cell therapy.